Evaluation of quality parameters and shelf life of Thai pork scratching “Kaeb Moo” - Thanapon Kitpot (2019)
Copyright © 2019 Thanapon Kitpot et al. This is an open access article distributed under the Creative Commons Attribution License Fried foods are one of the most favorite products worldwide because of their typical flavor and crispness. In Thailand, one of the most popular traditional foods is “Kaeb Moo,” a fried pork rind product typical of the Northern Region and widely consumed across the whole country. In this research, we monitored the quality change of Kaeb Moo during storage for 1 month and predicted the consumers' acceptance measuring texture, moisture contents, malondialdehyde (MDA) and hexanal contents, and peroxide values (PV) of frying oil, as this fried product undergoes a rapid hydrolysis and rancidity. The analyses were done on three types of Kaeb Moo: the first type was prepared in the lab using high-quality products, while the other two types were purchased from local markets in Thailand. It was found that rancidity variation during storage strongly depends on the frying process and product quality, as in 31 days the hexanal content only doubled (225%) in Kaeb Moo type 1, while reached 542% and 962%, in Kaeb Moo type 2 and type 3, respectively. The increase of rancidity was observed even if the peroxide values of frying oil were under the national regulation. At the end of shelf life, the properties of Kaeb Moo samples from predicting equations were as follows: 3.67-6.01% moisture contents, 0.396-0.503 µg/g MDA contents, 0.342-0.481 mg/kg hexanal contents, 50.01-60.08 kg·s linear distances (crispness), 36.01-48.83 mm rancid rating, and 43.72-45.38 mm crispness rating.